The Influence of Intellectual Capital and Knowledge Management on Organizational Performance in Lithuanian Software Companies - Atkočiūnienė, Zenona; Praspaliauskytė, Greta (Ekonomika, 2018)
[full article and abstract in English] In the contemporary information and knowledge society, it is important to evaluate the intangible organizational resources that generate long-term value for organizations. Among others, these include intellectual capital and management of knowledge. The research fields of intellectual capital and knowledge management address such issues as (but not limited to) the abilities of employees to create and accumulate knowledge, share and apply it in everyday activities, develop new, sustainable and long-term relationships with various stakeholders. During the last decade, there has been a shift in research toward linking these two previously separate fields of activity in order to demonstrate their interrelations and influence on organizational performance. However, this is problematic due to the difficulties of expressing the value of intellectual capital and knowledge management in a tangible form. The aim of this article is to analyze and define the influence of intellectual capital and knowledge management on organizational performance. For this task, we built a conceptual model for assessing the influence of intellectual capital and knowledge management on organizational performance, which was applied in a study conducted in IT companies operating in Lithuania.